2021
DOI: 10.1177/0269881120985147
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide signaling in the antidepressant mechanism of action of ketamine: A randomized controlled trial

Abstract: Ketamine is an N-methyl-D-aspartate receptor antagonist with rapid antidepressant effects. Studies suggest that inhibition of nitric oxide synthesis plays a role in the mechanism of action of ketamine. This randomized, placebo-controlled study investigated whether co-administration of sodium nitroprusside, a nitric oxide donor, compared to placebo, would attenuate the antidepressant and dissociative effects of ketamine. Sixteen ketamine responders were randomized to a double-blind infusion of ketamine co-admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Although, the signaling molecule NO has also been thought to play a role in inflammation as well as in ketamine’s antidepressant effects [ 35 , 62 ], a recent study suggested that the NO pathway may not play a primary role in these effects [ 63 ]. Multiple factors affect NO levels, including arginase activity, amino acid levels, NOS activity, and the presence of specific endogenous NOS inhibitors, such as ADMA and/or SDMA [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although, the signaling molecule NO has also been thought to play a role in inflammation as well as in ketamine’s antidepressant effects [ 35 , 62 ], a recent study suggested that the NO pathway may not play a primary role in these effects [ 63 ]. Multiple factors affect NO levels, including arginase activity, amino acid levels, NOS activity, and the presence of specific endogenous NOS inhibitors, such as ADMA and/or SDMA [ 34 ].…”
Section: Discussionmentioning
confidence: 99%